Economic Value of Brand : The Role of Gamification, Price Fairness Perception, and Service Quality on Brand Equity through Customer Trust of Wardah Cosmetics - Astuti R, Wanda Puspa Dewi; Komaludin, Ade; Surgawati, Iis (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to explore the economic value of brand equity by analyzing the roles of gamification, perceived price fairness, and service quality, with customer trust as a mediating variable. The research focuses on consumers of Wardah cosmetics on the Shopee e-commerce platform. A quantitative approach was employed using a purposive sampling technique with a total of 385 respondents. Data were collected through a structured questionnaire using a five-point Likert scale. The findings reveal that gamification, perceived price fairness, and service quality each have a positive and significant impact on customer trust. Furthermore, these three variables also directly influence brand equity positively and significantly. Customer trust itself has a significant mediating role in the relationship between the independent variables and brand equity. These results highlight that enhancing the interactive experience, ensuring fair pricing, and improving service quality contribute to building customer trust and, in turn, strengthening the economic value of the brand.